Kecerdasan Emosional Serta Dampaknya Untuk Kinerja Pegawai Dinas Pekerjaan Umum Dan Penataan Ruang Kota Pematangsiantar - Simatupang, Sudung; Efendi, Efendi (Jurnal Manajemen, 2020)
Form of service to the public. is the main task of the citizens of all citizens, because the form of service can be done well, good performance is also needed. Factors that influence performance Then, emotional intelligence can be agreed to control the individual within yourself. The results found that the variable does not require emotional intelligence and the variable called normal distribution with the provisions of the two-way test value> Sig 0.05, which means all variables are normally distributed. Furthermore, the results of the calculation of the path of positive calculation results with a value of Y = 9.885 + 0.805, which means the influence of emotional intelligence increases positive effect on employee performance, as well as the results of tests to answer the hypothesis (t test) shows the tcount data with a value of 10.898 for the variable emotional intelligence> with the results of ttable degree of trust received 1.99773 and the significance level of 0.000 <0.05, the conclusion of this study received an answer from the hypothesis <pre id="tw-target-text" class="tw-data-text tw-text-large XcVN5d tw-ta" style="unicode-bidi: isolate; font-size: 28px; line-height: 36px; background-color: #f8f9fa; border: none; padding: 2px 0.14em 2px 0px; position: relative; margin: -2px 0px; resize: none; font-family: inherit; overflow: hidden; width: 277px; white-space: pre-wrap; overflow-wrap: break-word; color: #222222;" dir="ltr" data-placeholder="Terjemahan">